2006
DOI: 10.1194/jlr.m500531-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of nascent HDL particles and microparticles formed by ABCA1-mediated efflux of cellular lipids to apoA-I

Abstract: The nascent HDL created by ABCA1-mediated efflux of cellular phospholipid (PL) and free (unesterified) cholesterol (FC) to apolipoprotein A-I (apoA-I) has not been defined. To address this issue, we characterized the lipid particles released when J774 mouse macrophages and human skin fibroblasts in which ABCA1 is activated are incubated with human apoA-I. In both cases, three types of nascent HDL containing two, three, or four molecules of apoA-I per particle are formed. With J774 cells, the predominant specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
197
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(215 citation statements)
references
References 64 publications
16
197
2
Order By: Relevance
“…e) ABCA1 might transfer bites of plasma membrane to nascent HDL particles [138]. This concept is consistent with the fact that phospholipids from both leaflets are represented in newly-formed HDL particles [131]. It is suggested that ABCA1 uses the energy of ATP hydrolysis to pump cytoplasmic phospholipids to the outer surface, thereby bending the bilayer outward.…”
Section: Cholesterol Export To High-density Plasma Lipoproteinssupporting
confidence: 62%
See 1 more Smart Citation
“…e) ABCA1 might transfer bites of plasma membrane to nascent HDL particles [138]. This concept is consistent with the fact that phospholipids from both leaflets are represented in newly-formed HDL particles [131]. It is suggested that ABCA1 uses the energy of ATP hydrolysis to pump cytoplasmic phospholipids to the outer surface, thereby bending the bilayer outward.…”
Section: Cholesterol Export To High-density Plasma Lipoproteinssupporting
confidence: 62%
“…Given that the ATP binding domain and putative substrate entry site of ABCA1 are oriented toward the endofacial leaflet, one might expect that cytoplasmic phospholipids would preferentially be transported to apoA-I. This hypothesis is undercut by the observation that, although ABCA1 might promote the transfer of cytoplasmic phospholipids to the cell surface, nascent HDL particles have a preponderance of exofacial lipid types [131][132][133]. c) It has been suggested that, because HDL particles are enriched in cholesterol, export draws selectively from sterol rich domains (rafts or caveolae).…”
Section: Cholesterol Export To High-density Plasma Lipoproteinsmentioning
confidence: 91%
“…67 Nascent HDL particles (7-17 nm in diameter) are originally discoidal and include 2-4 ApoA1 molecules. 68 In a case of high phospholipid content, generation of larger HDL particles is enhanced. 69,70 As ApoA1 is directly involved in lipid metabolism, this property is important for considering this apolipoprotein as one of key molecular players in the pathogenesis of cardiometabolic diseases, such as atherosclerosis.…”
Section: Involvement Of Apoa1 In Cholesterol Esterificationmentioning
confidence: 99%
“…Recent investigations into membrane proteins4, 19, 22, 25 have revealed that nanodiscs are a suitable tool to reconstitute membrane proteins in a native environment to solve their three‐dimensional structure with atomic resolution. They are derived from apolipoprotein A1 (ApoA‐1), which solubilises hydrophobic molecules, such as lipids and cholesterol, to deliver them to the liver through the blood and interstitial fluid as high‐density lipoprotein (HDL) particles 16, 27. A recent study by NMR spectroscopy shows how the structure of ApoA‐1 wraps around the hydrophobic part of the lipids to form a lipid‐bilayer patch in solution 5.…”
Section: Introductionmentioning
confidence: 99%